PERAN CUSTOMER SATISFACTION DALAM MEMEDIASI PENGARUH SIM TERHADAP REPUTASI PERGURUAN TINGGI - Husda, Nur Elfi (Bisman - Jurnal Bisnis & Manajemen, 2016)
This study aimed to examine the effect of Information Management System to customersatisfaction and reputation as well as see if there is a direct or indirect influence of the ManagementInformation System and reputation by using Structural Equation Modeling. Samples was studentsof Management as many as 360 of private universityin the city of Batam. The results showed thatthe Management Information System to significantly affect customer satisfaction, customersatisfaction significantly affect the standing, Management Information Systems significantly affectthe standing, Management Information Systems indirect effect on the reputation through customersatisfaction.